1995
DOI: 10.1046/j.1365-313x.1995.08050659.x
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Arabidopsis mutants deficient in flavonoid biosynthesis

Abstract: Eleven loci that play a role in the synthesis of flavonoids in Arabidopsis are described. Mutations at these loci, collectively named transparent testa (tt), disrupt the synthesis of brown pigments in the seed coat (testa). Several of these loci (tt3, tt4, tt5 and ttg) are also required for the accumulation of purple anthocyanins in leaves and stems and one locus (ttg) plays additional roles in trichome and root hair development. Specific functions were previously assigned to tt1-7 and ttg. Here, the results o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

21
491
2
3

Year Published

2001
2001
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 542 publications
(529 citation statements)
references
References 0 publications
21
491
2
3
Order By: Relevance
“…The function of the Arabidopsis TT4, TT5, and TT3 genes, encoding CHS, CHI, and DFR enzymes, has been inferred from the molecular analysis of multiple alleles (when available), from the effects on the expression of the corresponding mRNAs and proteins, and from the accumulation of particular intermediates in the pathway (Shirley et al, 1992(Shirley et al, , 1995Burbulis et al, 1996). To our knowledge, none of these mutations has been complemented with the corresponding wild-type genes from Arabidopsis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The function of the Arabidopsis TT4, TT5, and TT3 genes, encoding CHS, CHI, and DFR enzymes, has been inferred from the molecular analysis of multiple alleles (when available), from the effects on the expression of the corresponding mRNAs and proteins, and from the accumulation of particular intermediates in the pathway (Shirley et al, 1992(Shirley et al, , 1995Burbulis et al, 1996). To our knowledge, none of these mutations has been complemented with the corresponding wild-type genes from Arabidopsis.…”
Section: Discussionmentioning
confidence: 99%
“…Mutations that completely abolish flavonoid or anthocyanin production have been identified in genes encoding CHS, CHI, and DFR (Shirley et al, 1995;Shirley, 1996;Pelletier et al, 1999). This is in sharp contrast with other plants, where small multigene families encode many of the biosynthetic enzymes of the pathway (Dooner et al, 1991).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The tonoplast of vacuoles destined for storage of vegetative storage proteins or for pigment accumulation are marked by the presence of the vacuolar tonoplast intrinsic protein ␦-TIP alone, or a combination of ␦-plus ␥-TIP (Jauh et al, 1999). Presumably, vacuoles similar in function to pigment-containing vacuoles are the site of PA accumulation in cells.In Arabidopsis, mutants affecting flavonoid synthesis have been identified, and include the tt mutants (Koornneef, 1990;Shirley et al, 1992Shirley et al, , 1995. Many of the tt mutants were identified in mutant populations of Arabidopsis because of altered seed coat color or alterations to dormancy and germination characteristics WinkelShirley, 2001).…”
mentioning
confidence: 99%
“…In some recent studies a direct relationship between up regulation of DFR expression and higher accumulation of anthocyanin had been documented 14 . Several studies have demonstrated that deactivation or lesser expression of the DFR gene results in the loss of anthocyanin accumulation in mutants of barley and Arabidopsis 15,16 . Studies have reported that anthocyaninshave the ability to scavenge active oxygen radicals 17 due to its antioxidant activity.…”
Section: Introductionmentioning
confidence: 99%